2020
DOI: 10.3233/shti200710
|View full text |Cite
|
Sign up to set email alerts
|

A Decentralized Framework for Biostatistics and Privacy Concerns

Abstract: Biostatistics and machine learning have been the cornerstone of a variety of recent developments in medicine. In order to gather large enough datasets, it is often necessary to set up multi-centric studies; yet, centralization of measurements can be difficult, either for practical, legal or ethical reasons. As an alternative, federated learning enables leveraging multiple centers’ data without actually collating them. While existing works generally require a center to act as a leader and coordinate computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In a previous study, we demonstrated that odd-ratios and their confidence intervals resulting from a decentralized logistic regression were consistent with the ones obtained with the traditional centralized model [3]. Other studies implemented Support-Vector Machine, Principal Components Analysis or Neural Networks using FL [4].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In a previous study, we demonstrated that odd-ratios and their confidence intervals resulting from a decentralized logistic regression were consistent with the ones obtained with the traditional centralized model [3]. Other studies implemented Support-Vector Machine, Principal Components Analysis or Neural Networks using FL [4].…”
Section: Introductionsupporting
confidence: 76%
“…We did not address the choice of a specific tool or library to perform federated computations. We note that existing tools [3,8] could fit within our framework, but usually only tackle the model training step, and are for the most still limited to simulated network environments.…”
Section: Discussionmentioning
confidence: 99%
“…The material provided here could be used and enhanced by other centers. In combination with federated learning [ 47 ], the OMOP CDM provides tools needed for conducting reproducible research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently shown that FL models outperformed traditional single-institution ML architectures [148,[151][152][153][154][155][156] and may be comparable to models built via central learning (centralized database) [137,138,[143][144][145][146][147][148][149][150]. In some studies, the FL approach has even been shown to be superior to alternative collaborative learning methods [137,145].…”
Section: Federated Learningmentioning
confidence: 99%